CLINICOPATHOLOGICAL FACTORS ASSOCIATED WITH 10-YEAR SURVIVAL FOLLOWING RADICAL SURGERY FOR GASTRIC CANCER - Aziziy , A.A.; Abdikhakimov , A.N. (International Conference on Medicine & Agriculture, 2026)
Despite continuous advances in multimodal treatment, gastric cancer remains one of the leading causes of cancer-related mortality worldwide. Radical surgery is the cornerstone of treatment for locally advanced gastric cancer; however, only a limited proportion of patients achieve long-term survival exceeding 10 years. Conventional TNM staging does not fully explain differences in long-term outcomes among patients with similar disease stages.